Narasi Komunikasi Kesehatan Penanganan Covid-19 dan Plasma Konvalesen: Satuan Gugus Tugas dan Penyintas di UPN “Veteran” Yogyakarta - Virginia Ayu Sagita; Medi Trilaksono Dwi Abadi; Mochammad Fauzul Haq; Dufadila Yusrin; Nadya Alifta (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
The number of positive cases is increasing every day. This shows that the government's communication policy must be a serious concern for handling the Covid-19 pandemic. The chairman of the Covid-19 task force in Indonesia by the Covid-19 handling decision regulation Number 9 of 2021 requires that the Indonesian people must self-isolate if they are asymptomatic or have mild symptoms at home or the shelter provided by the Covid-19 task force unit. local. The role of the Covid-19 task force is very much needed by the community to access needs when they are suspected patients and to provide information to the public. This study reveals the communication narrative used by the Covid-19 task force to patients and survivors in the UPNVY environment. The health communication narrative from the UPNVY Covid-19 task force unit is needed by the UPN Veteran Yogyakarta academic community. This research uses narrative theory with a data collection method using purposive sampling. Data collection was carried out by interviewing the chairman and deputy chairman of the Covid-19 task force, patients, and survivors who were willing to provide information related to this research. The results of this study indicate that the Covid-19 task force unit communicates or narrates the handling of Covid-19 and convalescent plasma donors with communication strategies that are by needs. The communication narrative carried out by the task force is that the narrative is used as a message maker to convey information on the handling of Covid-19 and information to donate convalescent plasma to survivors.